2011
DOI: 10.1002/etc.695
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of acute and chronic gamma‐irradiation on zebrafish cells and consequences for embryo development

Abstract: The effects of radiation on biological systems have been studied for many years, and it is now accepted that direct damage to DNA from radiation is the triggering event leading to biological effects. In the present study, DNA damage induced by acute or chronic irradiation was compared at the cellular (zebrafish [Danio rerio] cell line ZF4) and developmental (embryo) levels. Zebrafish ZF4 cells and embryos (at 3 h postfertilization) were exposed within ranges of acute doses (0.3-2 Gy/d) or chronic dose rates (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…This initial toxicity assay provided baseline toxicity of IR in our laboratory at the specific doses at the specific developmental time point of exposure for comparison to previous completed studies with the zebrafish model system. Our findings are similar to those reported in the literature for radiation exposure at this developmental time point, while exposure at earlier developmental stages is reported as more toxic (McAleer et al, 2005; Geiger et al, 2006; Pereira et al, 2011). McAleer et al (2005) and Geiger et al (2006) observed that lethal effects of IR were inversely proportional to embryonic age with earlier embryonic stages (e.g., 2–6 hpf) being more sensitive to lethality than later embryonic stages (e.g., 8–24 hpf).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This initial toxicity assay provided baseline toxicity of IR in our laboratory at the specific doses at the specific developmental time point of exposure for comparison to previous completed studies with the zebrafish model system. Our findings are similar to those reported in the literature for radiation exposure at this developmental time point, while exposure at earlier developmental stages is reported as more toxic (McAleer et al, 2005; Geiger et al, 2006; Pereira et al, 2011). McAleer et al (2005) and Geiger et al (2006) observed that lethal effects of IR were inversely proportional to embryonic age with earlier embryonic stages (e.g., 2–6 hpf) being more sensitive to lethality than later embryonic stages (e.g., 8–24 hpf).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies using the zebrafish model system to evaluate ionizing radiation exposure have been used to assess general toxicity (e.g., mortality, hatching rates, gross morphological alterations, DNA damage, and apoptosis) (e.g., Bladen et al, 2007; Choi et al, 2010a,b, 2012a, 2013; Pereira et al, 2011; Sorrells et al, 2012; Yu et al, 2012; Toruno et al, 2014), to screen radiation protectors (McAleer et al, 2005; Geiger et al, 2006), and to assess the long-term effects on liver gene expression (Jaafar et al, 2013). To the best of our knowledge, no work is published on the effect of IR to heart rate using the zebrafish model.…”
Section: Discussionmentioning
confidence: 99%
“…Fish as a large class of the vertebrates are one of the most studied groups of animals in toxicology and radiobiology because of their key position in aquatic ecosystems (Real et al 2004, Pereira et al 2011, Smith et al 2011a, Tsyusko et al 2011, Mothersill and Seymour 2012, Olsvik et al 2012. Th ey are considered to be relatively radioresistant (Choppin et al 2002), but close examination of the data suggest that the radioresistance is limited to adult fi sh and that lethality is the endpoint (Whicker and Schultz 1982).…”
Section: Introductionmentioning
confidence: 97%
“…Th ey are considered to be relatively radioresistant (Choppin et al 2002), but close examination of the data suggest that the radioresistance is limited to adult fi sh and that lethality is the endpoint (Whicker and Schultz 1982). Recent studies using embryos of zebrafi sh, salmonids and earthworms , Yum et al 2010, Hertel-Aas et al 2011a, Pereira et al 2011) suggest a very sensitive response to radiation and other mutagens. Th is means that in the wild, the fi sh could be impacted by exposure to radiation at environmentally relevant levels, with consequent eff ects on aquatic food webs.…”
Section: Introductionmentioning
confidence: 99%
“…Además, se encontró evidencia de sub unidades de Ku70 en una amplia diversidad de organismos marinos tanto vertebrados como invertebrados (Kanungo et al 1999, Pereira et al 2011, Rhee et al 2012). …”
Section: Sca5 (Ompb)unclassified